Preclinical evidence and potential mechanisms of tanshinone ⅡA on cognitive function in animal models of Alzheimer’s disease: a systematic review and meta-analysis - Rong, Yuanhang; Li, Qinqing; Du, Yuzhong; Wang, Wenting; Su, Wenna; Zhang, Junlong; He, Wenbin (Frontiers in Pharmacology, 2025)
BackgroundTanshinone ⅡA (Tan ⅡA) is a monomer extracted from Salvia miltiorrhiza Bunge. Animal studies have demonstrated its potential in providing cognitive protection in Alzheimer’s disease (AD), but the overall effects remain inconclusive, and its multiple mechanisms have not been systematically summarized.ObjectiveThis systematic review and meta-analysis (SR/MA) aimed to evaluate the overall effects of Tan ⅡA on cognitive function in AD animal models and to summarize the mechanisms.MethodsSeven databases (PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Chinese Biological Medical Disc, Chongqing VIP, and Wanfang databases) and grey literature were retrieved. Risk of bias was evaluated following the Systematic Review Center for Laboratory Animal Experiments. The mean difference (MD) or standard mean difference (SMD) with 95% confidence intervals (CIs) were used to evaluate the effect of Tan ⅡA on cognitive function, neuropathology, neuroinflammation, oxidative stress, apoptosis, and neural/synaptic plasticity, with P < 0.05 considered a significant difference. The effect and potential mechanisms of Tan ⅡA were demonstrated by performing multiple subgroup analyses.ResultsNineteen studies involving 581 AD animals were identified. The included studies showed satisfactory reporting quality but had certain risks of bias in methodology. Tan ⅡA ameliorated cognitive deficits, evidenced by reducing escape latency (MD = −17.94 s; 95% CI: −22.92 to −12.96) and increasing time spent in the target quadrant (MD = 10.69 s; 95% CI: 7.32–14.07). It attenuated neuropathological damage by reducing amyloid-β (Aβ) plaques in thioflavine S staining (SMD = −3.46; 95% CI: −5.65 to −1.26) and increasing neuronal density in Nissl staining (SMD = 2.82; 95% CI: 2.11–3.52) and NeuN staining (SMD = 2.89; 95% CI: 1.71–4.08). Tan ⅡA also demonstrated anti-inflammatory effects through downregulation of pro-inflammatory cytokines [tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6)] and antioxidant stress properties by increasing superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) levels while reducing reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Additionally, it exhibited antiapoptotic effects by increasing the B-cell lymphoma-2/Bcl-2-associated X protein (Bcl-2/Bax) ratio and decreasing Caspase-3 expression. Moreover, treatment improved neuronal/synaptic plasticity by upregulating postsynaptic density-95 (PSD-95) and brain-derived neurotrophic factor (BDNF) levels.ConclusionTan ⅡA could improve cognitive function and neuropathology through multiple mechanisms. This suggests that Tan IIA may serve as a viable candidate for the development of therapeutic strategies for AD.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024588415.